A Systemic Functional Analysis of the Nominal Group in Selected Eco-Critical Poems of Ebi Yeibo and G’ebinyo Ogbowei - Ojarikre, Anthony (NIU Journal of Humanities, 2023)
This paper examines the Nominal Group in the ecopoetry of Ebi Yeibo and G’ebinyo Ogbowei. Both poets are of the Niger Delta literary tradition of protest literature. This literature is a reaction to the brazen exploitation of petroleum resources in the Niger Delta without compensation and environmental impact assessment by the Nigerian government and the international oil companies. Three representative poems are selected from different collections of the two poets. They are analysed using Systemic Functional Grammar as theoretical framework. The systemic functional analysis of the Nominal Group brings out the eco-critical features of the poems. An analysis of the MHQ structures throws up the vexed issue of environmental injustice and brings to the fore the struggle of the Niger Delta people for resource control. Keywords: Niger Delta, Hydrocarbon, Environmental Injustice, Resource Control, Ecocriticism